Filling of carbon nanotubes and nanofibres - Gately, Reece D.; in het Panhuis, Marc (Beilstein Journal of Nanotechnology, 2015)
The reliable production of carbon nanotubes and nanofibres is a relatively new development, and due to their unique structure, there has been much interest in filling their hollow interiors. In this review, we provide an overview of the most common approaches for filling these carbon nanostructures. We highlight that filled carbon nanostructures are an emerging material for biomedical applications.
Keywords: applications; carbon nanostructures; filling; nanofibers; nanotubes